Historiadores de fé: agnosticismo e religiosidade em Jean Delumeau e Souto Maior. - Santana, Anselmo Jeronimo de (2013)
This work brings issues relating to science and religion, history and religion of these two approaches to potential fields of know. For contribute to the thread was posted two historians: Jean Delumeau and Souto Maior. Delumeau is a French historian who has done research on the Christianity in particular the question of the discourse of fear and led to a tradition blame.De atheist, he is Catholic and in his book The Reason for My Faith, sets out his beliefs. This is the Brazilian historian Armando Souto Maior the end of his life left the agnostic vision to become spirit, writing the book: Before and After Kardec, that changed with the symbolic field, becoming religious and making a series of actions around the spirit and history. The history, the historian, teacher and historian, in his professional activity is focused in front of an entire pathway that comes from the nineteenth century and the challenges of the history of the twentieth century and the whole construction of the XXI century and the prospect of a further with other subjects in the study of religion, of the science and religion, the faith and its implications in the production of scientific knowledge. The issue of religion and the field of religion, not just the field of religion, the religious phenomenon, seen in its full reality. The science and religion, are fields of knowledge, which were many moments and conflict, and the speeches of both observed in the context of history from the Egyptians and other peoples.